Gym’s hybrid system for off-grid renewable energy solutions - Abdelfattah El Azzab; Abdelmounime El Magri; Rachid Lajouad; Ilyass El Myasse; Aziz Watil; Hassan Ouabi (Institute of Advanced Engineering and Science, 2024)
The primary objectives behind transitioning from fossil fuels to green energy sources, with a particular focus on reducing both electricity costs and carbon emissions. This transition has prompted various sectors and sports bikes, to embrace renewable energy alternatives, with a specific emphasis on technologies such as photovoltaic systems, energy storage solutions, and power generation from machines. The core subject of investigation in this paper is the application of renewable energy sources within sports bikes, with a particular emphasis on a hybrid system. This hybrid system incorporates DC/DC, AC/DC, and DC/AC converters to meet the energy requirements of the facility. The central aim of the research is to identify the most economically efficient scale for a self-sufficient hybrid photovoltaic system that integrates stationary generators and battery storage. The research seeks to optimize the balance between cost-effectiveness and sustainable energy provision in the context of sports facilities.